ANCANGAN MODEL KERANGKA TEORI KESANTUNAN YANG EFEKTIF MENGKAJI BUDAYA BAHASA-BAHASA HERITAGE DI ASIA: REVIEW TERHADAP KEUNIVERSALITASAN KERANGKA TEORI KESANTUNAN BROWN & LEVINSON - Abdul Hakim Yassi (Linguistik Indonesia, 2017)
The article revisits the effectiveness and compatibility of Yassi’s politeness theoretical framework (1996, 2011), adapted from Brown & Levinson’s (1978, 1987, hereafter; B&L) and Scollon & Scollon’s (1995), in studying politeness system of heritage languages in Indonesia and Asia in general. Data, transcription of recorded utterances of some heritage languages in South and West Sulawesi, were analyzed employing Yassi’s framework. The study reveals that B&L’s fails to distinguish a kinship-based interaction from those of non-kinship one. Intimacy on kinship relations, like interaction among brother-sisters denoted different behaviors from those of among friends. The former tended to be asymmetrical  where the elder employed positive politeness and the younger used negative politeness. The latter tended to be symmetrical where all participants tended to employ positive politeness. Similar behavior also denoted by a kinship-based asymmetrical interaction, for instance, interaction among husband-wife-children which is completely different from those of non-kinship one such as interaction between bosses and staff.